KARAKTERISTIK FISIK DAN KIMIA SUSU JAGUNG MANIS PADA BERBAGAI LAMA PEREBUSAN - Rahmat Muhajir; Abdul Rahim; Gatot Siswo Hutomo (Universitas Tadulako, 2014)
The research of the objectives is know of boiling time sweet corn kernels on the physical, chemical and organoleptic properties of corn milk that quality to produce. The research were used a completely randomized design (CRD) with using boiling time sweet corn as a treatment that consisting of four levels, i.e 30, 45, 60 and 75 min. The treatment was repeated three times, so that would be obtained 12 trials. The treatment were effected significantly further tested with real honest test (HSD) at 5%. The results showed that the yields (75.22%) of sweet corn highest at the of 60 min boiling time, the viscosity (983 cp) of highest at the 45 min and the emulsion stability (16.41%) of the best it was 30 min boiling time. The chemical properties were founded of the best such as water content (78.5%) at 60 min, sugar content (14.4%) at 45 min, protein content (3.36%) at 60 min, fiber content (0.45%) at 75 min and ash content (0.22%) at 60 min. Key Words : Boiling, corn milk, physical and chemical characteristics, sweet corn.